(8.83-.33y)+4y=106

Simple and best practice solution for (8.83-.33y)+4y=106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8.83-.33y)+4y=106 equation:


Simplifying
(8.83 + -0.33y) + 4y = 106

Remove parenthesis around (8.83 + -0.33y)
8.83 + -0.33y + 4y = 106

Combine like terms: -0.33y + 4y = 3.67y
8.83 + 3.67y = 106

Solving
8.83 + 3.67y = 106

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8.83' to each side of the equation.
8.83 + -8.83 + 3.67y = 106 + -8.83

Combine like terms: 8.83 + -8.83 = 0.00
0.00 + 3.67y = 106 + -8.83
3.67y = 106 + -8.83

Combine like terms: 106 + -8.83 = 97.17
3.67y = 97.17

Divide each side by '3.67'.
y = 26.47683924

Simplifying
y = 26.47683924

See similar equations:

| 2=x+6 | | 4x+5x-9=3x+x+6 | | 3(x-2)-4(x+1)= | | x=-1/2 | | x=-1/2 | | y^2-4y=4 | | 6y-4=2y+10 | | 3x+39=13x-37 | | 2a^2-12a+18=14 | | a-8=13 | | x^2+20x=9 | | h=25-9t | | 6(x+5)-(4x-5)= | | 9y-5=7+8y | | 240000=80x | | 6-(3x-3)-[2(-4x-1)]=-(-3x+2) | | 4y=15-y | | 9y-5(y-2)=12 | | 2x^3-x^2-3x+1=0 | | -x^4+5x^3+3x^2-13x=10 | | 699=c*(1+.30) | | 699=c*.30 | | 160=t^2 | | 1500x=120000 | | 262=h^2 | | 7x^2=847 | | x^2+6-4=0 | | Q=40-2P | | 9m-4=-(18)+2m | | 6x+5=2x+-3 | | 6x-7x-3=15 | | y=4(1) |

Equations solver categories